Are monuments of technology and engineering in Poland still a “second-class” heritage? Historical outline and current problems - Walczak, Bartosz M. (Protection of Cultural Heritage, 2016)
This article explains issues pertaining to protection of materials that are relevant by their use or their invention in the view of changing socio-economic conditions and evolution of approaches to historic preservation. The author discusses sources of problems, provides historical outline of research studies and presents the current situation in Poland. Furthermore, the article focuses on problems related to the definition of industrial and engineering heritage and assessment of its values. Particular emphasis was placed upon authenticity and classification of materials that are relevant by their use or their invention. The author of this article also highlights that this type of heritage and other historic monuments and sites should be considered equal. Additionally, this paper suggests how crucial the concept of integrated area-based protection is to efficient historic preservation of materials that are relevant by their use or their invention.